HOW LITERATURE CAN ENHANCE CRITICAL THINKING SKILLS IN ENGLISH LEARNERS (Ustozlar uchun, 2025)
This article examines the role of literature in developing critical thinking skills among English learners. Through analysis of literary texts, learners are encouraged to question, interpret, and reflect on diverse perspectives, enhancing their understanding and engagement. The paper explores strategies such as Socratic questioning, thematic analysis, and character study to foster critical thinking in language learners. By incorporating literature into language instruction, teachers can create a platform for learners to analyze complex ideas, make connections, and engage in reflective thinking.